The Developing Discourse of Educational Philosophy in Indonesia 2020-2024: Systematic Literature Review - Gusti Anggraini; Muhammad Kristiawan; Bayu Insanistyo (Journal of Social Work and Science Education, 2026)
This study highlights the state of research in the philosophy of education in Indonesia during the 2020–2024 period through a Systematic Literature Review (SRB) using the PRISMA framework. The analysis process included the identification, screening, and synthesis of primary literature from various major databases, such as Google Scholar, DOAJ, and Garuda, to obtain a comprehensive overview of the trends, themes, and evolution of contemporary educational philosophy discourse. The review results indicate that key thematic clusters include the revitalization of local thinkers, responses to the digital era, and character education, which have become dominant focuses in current research developments. Indonesian educational philosophy discourse is typically value-oriented and contextual, emphasizing the integration of Pancasila values, local wisdom, and social ethics into educational practice. However, significant gaps remain, such as the lack of analysis based on student age levels. The limited representation of Western philosophical schools and the fragmented research landscape, which has not yet comprehensively mapped the relationships between themes, underscore the need for more systematic, holistic, and multidimensional research to support the development of educational theory, practice, and policy that adapts to global challenges, digital transformation, and the need to develop an intelligent, critical, and character-driven generation. Therefore, this research not only contributes to the literature mapping but also serves as a foundation for innovative strategies in education in Indonesia.